Post-Odontoma autotransplantation of an impacted tooth: A case report - Waikhom Robindro Singh; Kirankumar Aheibam; Anthopia Nameirakpam (Elsevier, 2015)
After years of relegation by dental implants, autotransplantation has recently become more popular because of a better understanding of its science. The prognosis of autotransplantation primarily depends upon the presence of an intact alveolar bone at the transplant site and the regeneration of a functional periodontal ligament of the transplant. Replacement of an unsalvaged or a missing tooth by a natural tooth with normal periodontium within a short duration of treatment is the ultimate challenge of autotransplantation. Meanwhile, Platelet Rich Fibrin (PRF) is popular as a biomaterial which helps in the regeneration of bone and periodontal tissues. To improve the prognosis, and also shorten the treatment time in a rare case of autotransplantation of an impacted tooth in a post-odontoma site, we did a two-stage surgical procedure aided by synthetic bone granules (Biograft) and PRF. The clinical and radiological findings at 6 months follow-up showed good result and promise.